Antimicrobial Activities of Phenolic Extracts Derived from Seed Coats of Selected Soybean Varieties. Issue 3 (8th February 2017) - Abutheraa, Rajaa; Hettiarachchy, Navam; Kumar‐Phillips, Geetha; Horax, Ronny; Chen, Pengyin; Morawicki, Ruben; Kwon, Young Min
Abstract: Soybean hulls or seed coats consist of complex carbohydrates, proteins, lipids, and polyphenols such as anthocyanidins, proanthocyanidins, and isoflavones. The polyphenolics in the seed coats give them various colors such as black, brown, green, yellow, or even a mottled appearance. In this study, the antimicrobial effects of phenolic extracts from the seed coats of different colored soybeans (yellow, dark brown, brown, and black) were evaluated against foodborne pathogens such as Salmonella Typhimurium, Escherichia coli O157:H7, and Campylobacter jejuni in broth‐cultures as well as on chicken skin. The highest total phenolic content was observed for the phenolic extract from soybean variety (R07‐1927) with black colored seed coat (74.1 ± 2.1 mg chlorogenic acid equivalent [CAE]/g extract) and was significantly different ( P <0.0001) from the extract of the conventional soybean variety (R08‐4004) with yellow colored seed coat (7.4 ± 1.2 mg CAE/g extract). The extract from black colored soybean produced reductions of 2.10 ± 0.08 to 2.20 ± 0.08‐log CFU/mL for both E. coli O157:H7 and C. jejuni after 3 d when incubated in broth‐culture having 4‐log CFU/mL of bacteria, whereas a 6 d incubation was found to reduce S . Typhimurium and E. coli O157:H7 at 2.03 ± 0.05 and 3.3 ± 0.08‐log CFU/mL, respectively. The extract also reduced S . Typhimurium and E. coli O157:H7 attached to chicken skin by 1.39 ± 0.03 and 1.24 ± 0.06‐log CFU/g, respectively, upon incubation for 6 d. Soybean seed coat extracts may have a potency as antimicrobial agents to reduce foodborne bacteria contaminating poultry products.